2001
DOI: 10.1161/hs1101.097401
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Motor Network Overactivation After Striatocapsular Stroke: A Longitudinal PET Study Using a Fixed-Performance Paradigm

Abstract: Background and Purpose-Although excessive brain activation during affected hand motion after stroke is well documented, its time course has been rarely studied, and when studied, this has either been with passive movement or with active but cognitively complex task and uncontrolled performance over time, complicating interpretation. Methods-According to a prospective and longitudinal design, we studied 5 right-handed patients with right-sided hemiparesis due to first-ever left striatocapsular infarction. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
189
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(221 citation statements)
references
References 33 publications
21
189
0
5
Order By: Relevance
“…This finding agrees with several previous studies, which reported that with functional recovery, focusing of the initial over-activation seen in stroke patients mainly occurs to the ipsilesional M1 (Nelles et al, 1999;Marshall et al, 2000;Calautti et al, 2001;Cramer et al, 2002;Feydy et al, 2002;Ward et al, 2003, Binkofski & Seitz, 2004, Carey et al, 2005. Greater and widespread neural activation has been reported in previous studies of stroke recovery, both cross-sectional and longitudinal (Chollet et al, 1991;Weiller et al, 1992;Cramer et al, 1997;Cramer 1999;Nelles et al, 1999;Marshall et al, 2000;Calautti et al, 2001;Ward et al, 2003, Carey et al, 2005. It seems that the system is somehow "upregulated" for execution of any movement and it is possible that such an increase in neural activity is essential to send sufficient signal to the motor neurons downstream.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding agrees with several previous studies, which reported that with functional recovery, focusing of the initial over-activation seen in stroke patients mainly occurs to the ipsilesional M1 (Nelles et al, 1999;Marshall et al, 2000;Calautti et al, 2001;Cramer et al, 2002;Feydy et al, 2002;Ward et al, 2003, Binkofski & Seitz, 2004, Carey et al, 2005. Greater and widespread neural activation has been reported in previous studies of stroke recovery, both cross-sectional and longitudinal (Chollet et al, 1991;Weiller et al, 1992;Cramer et al, 1997;Cramer 1999;Nelles et al, 1999;Marshall et al, 2000;Calautti et al, 2001;Ward et al, 2003, Carey et al, 2005. It seems that the system is somehow "upregulated" for execution of any movement and it is possible that such an increase in neural activity is essential to send sufficient signal to the motor neurons downstream.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, if activation in the contralesional M1 persists during the initial post-stroke period (Marshall et al, 2000;Calautti et al, 2001;Johansen-Berg et al, 2002a;Carey et al, 2002) and even after good recovery, and this area does not relay direct corticomotoneuronal connections, it is reasonable to conclude that contralesional M1 activation arises out of altered intracortical and transcallosal interactions. An alternative explanation is that contralesional M1 activation arises from top-down activation from higher order areas, and is an epiphenomenon not contributing to recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contralesional shift of activation may return to ipsilesional S1M1 activation with functional gains (Feydy et al, 2002;Takeda et al, 2007), but worse outcome may correlate with a shift in the balance of activation toward the contralesional S1M1 (Calautti et al, 2001;Feydy et al, 2002;Zemke et al, 2003). Thus, the patterns of cerebral activation evoked by active hand movement show impaired organization and reorganization of brain sensorimotor network, and best recovery may depend on how much original motor system is reusable.…”
Section: Activation Of Sensorimotor Network By Active Motor Taskmentioning
confidence: 99%
“…Initial cross-sectional studies at chronic stages of stroke have demonstrated that the pattern of brain activation is different between paretic and normal hand movements, and suggested that long-term recovery is facilitated by compensation, recruitment and reorganization of cortical motor function in both damaged and non-damaged hemispheres (Chollet et al, 1991;Weiller et al, 1992;Cramer et al, 1997;Cao et al, 1998;Ward et al, 2003a). Subsequent longitudinal studies from subacute to chronic stages (before and after rehabilitation) have revealed a dynamic, bihemispheric reorganization of motor network, and emphasized the necessity of successive studies (Marshall et al, 2000;Calautti et al, 2001;Feydy et al, 2002;Ward et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%